The role of iot technologies in Malaysia during the Covid-19 pandemic: A mini-review - Nur Amalina Muhamad; Fazlinashatul Suhaidah Zahid; Norhalida Othman; Nor Diyana Md Sin (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Covid-19 global infection has significantly influenced people’s health, resulting in sudden changes in lifestyle through social exclusion and isolation. To break the transmission and terrifying health threat of Covid-19, the Malaysian Government imposed a Movement Control Order (MCO) starting March 18, 2020, by restricting movement and contact. The Covid-19 pandemic emphasized the importance of the digital inclusion agenda, and the application of Internet of Things (IoT) services has given tremendous benefits in various disciplines, as it helps maintain physical distance during the pandemic. Modern lifestyles are being transformed by the IoT revolution by embracing technological, economic, and social prospects. In fact, many sectors in Malaysia would be transformed through the application of IoT, particularly in productivity, and services. Thus, this review paper discusses IoT’s most recent breakthroughs and applications that are used in Malaysia during the Covid-19 crisis. Furthermore, it investigates current IoT implementation and discusses the potential impact of the pandemic on the application of IoT in terms of technology trends and economic impact. IoT is worth mentioning as one of the technologies demonstrating its importance and capabilities in mitigating the severity of the pandemic within the country. This article delves into the applications, social and economic impact, and barriers to the widespread adoption of IoT in the Covid-19 pandemic. This review paper will be useful to academic researchers, business professionals, organizations in various sectors, and anyone interested in determining IoT services’ impact on pandemics.